Effect of Career Development, Compensation and Leadership Style on Job Satisfaction - Sinta Sundari Heriyanti; Intan Krisma (Kusuma Negara Business School, 2022)
Career development, compensation and leadership style are directly related to employee job satisfaction. Career development, compensation and leadership style perceived by employees can reduce job satisfaction or increase employee job satisfaction. Employees who are satisfied with the work obtained will be motivated to improve performance so that it will have an impact on increasing the performance of the company or organization as a whole. Therefore, it is expected that the organization must be aware of and create a management system that takes into account the factors that influence the work attitude of employees in order to achieve the goals of the organization itself. This study aims to analyze the effect of career development, compensation, and leadership style variables on employee job satisfaction. This research was conducted at PT Sinar Putra Metalindo, Cikarang. The number of samples set is 98 respondents with sampling using the saturated sample method. Measurements in the questionnaire. The data analysis method used is multiple linear regression using the SPSS 26 application program. The results of testing the first hypothesis show that career development has a positive and significant effect on employee job satisfaction. The results of testing the second hypothesis show that compensation has a positive and significant effect on employee job satisfaction. The results of testing the third hypothesis show that leadership style has a positive and significant effect on employee job satisfaction.